Microbial Community Dynamics During the Non-filamentous Fungi Growth-Based Fermentation Process of Miang, a Traditional Fermented Tea of North Thailand and Their Product Characterizations - Kridsada Unban (2020)
© Copyright © 2020 Unban, Khatthongngam, Pattananandecha, Saenjum, Shetty and Khanongnuch. Miang, a traditional fermented tea leaf (Camellia sinensis var. assamica) consumed in northern Thailand, was simulated in laboratory conditions using non-filamentous fungi process (NFP) and microbial community was periodically investigated for over 6 months of fermentation by both culture-dependent and -independent techniques. The viable cell numbers of lactic acid bacteria (LAB), yeast, and Bacillus enumerated by the culture-dependent technique markedly surged over 3 days of initial fermentation and then smoothly declined by the end of fermentation. LAB were found as the main microbial population throughout the fermentation period followed by yeast and Bacillus. High-throughput sequencing of microbial community during fermentation revealed that Firmicutes (86.9–96.0%) and Proteobacteria (4.0–12.4%) were the dominant bacterial phyla, whereas Ascomycota was found to be the main fungal phylum with an abundance of over 99% in the fungal community. The dominant bacterial family was Lactobacillaceae (39.7–79.5%) followed by Acetobacteraceae, Enterobacteriaceae, Bacillaceae, Aeromonadaceae, Staphylococcaceae, Moraxellaceae, Clostridiaceae, Exiguobacteraceae, Streptococcaceae, and Halomonadaceae. Meanwhile, the main fungal family was incertae sedis Saccharomycetales (75.6–90.5%) followed by Pichiaceae, Pleosporaceae, Botryosphaeriaceae, Davidiellaceae, Mycosphaerellaceae, and Saccharomycodaceae. In addition, Lactobacillus (29.2–77.2%) and Acetobacter (3.8–22.8%), and the unicellular fungi, Candida (72.5–89.0%) and Pichia (8.1–14.9%), were the predominant genera during the fermentation process. The profiles of physical and chemical properties such as Miang texture, pH, organic acids, polysaccharide-degrading enzyme activities, and bioactive compounds have rationally indicated the microbial fermentation involvement. β-Mannanase and pectinase were assumed to be the key microbial enzymes involved in the Miang fermentation process. Total tannin and total polyphenol contents were relatively proportional to the antioxidant activity. Lactic acid and butyric acid reached maximum of 50.9 and 48.9 mg/g dry weight (dw) at 9 and 63 days of fermentation, respectively. This study provided essential information for deeper understanding of the Miang fermentation process based on the chemical and biological changes during production.